1996
DOI: 10.2134/jeq1996.00472425002500010005x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Transport of Pesticides through Field Soils—A Review

Abstract: Much information is available in the literature about pesticide transport through soils at the field scale. The purpose of this study is to review the literature with a focus on pesticide leaching to groundwater. The literature was compiled and discussed with respect to different factors that influence pesticide leaching. Pesticide leaching below the root zone has been demonstrated in sandy as well as in loamy soils. Particularly in loamy soils, there is evidence that even strongly adsorbing chemicals can move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
281
1
32

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(331 citation statements)
references
References 0 publications
17
281
1
32
Order By: Relevance
“…This effect is independent of land use and soil texture. The shortened nutrient discharge pathway leads to a reduced denitrification capacity of tile drained landscapes and high values for nutrient or pesticide emission into surface waters (FLURY, 1996;GÄRDENÄS et al, 2006;JARVIS, 2007JARVIS, , 2002MACRAE et al, 2007;TIEMEY-ER et al, 2008, 2009). Measures to reduce this high level of agricultural emissions are often discussed (e.g., KREINS et al, 2010;MANDER et al 2000;SAVCHUK et al, 2008;THIEU et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This effect is independent of land use and soil texture. The shortened nutrient discharge pathway leads to a reduced denitrification capacity of tile drained landscapes and high values for nutrient or pesticide emission into surface waters (FLURY, 1996;GÄRDENÄS et al, 2006;JARVIS, 2007JARVIS, , 2002MACRAE et al, 2007;TIEMEY-ER et al, 2008, 2009). Measures to reduce this high level of agricultural emissions are often discussed (e.g., KREINS et al, 2010;MANDER et al 2000;SAVCHUK et al, 2008;THIEU et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, particle detachment and soil erosion is clearly a threshold process (Hicks et al, 2000;Salles et al, 2000;Hairsine et al, 2002;Shao et al, 2005;Maerker et al, 2008;Scherer, 2008;Ternat et al, 2008), which is controlled by rainfall intensity, shear stress due to overland flow and soil stability. Infiltration, vertical flow and transport of contaminants in field soils may be observed in two qualitatively different modes, namely in preferential pathways or in a slow form in the soil matrix continuum (Bouma, 1981;Beven and Germann, 1982;Edwards et al, 1989;Flury et al, 1994Flury et al, , 1996Stamm et al, 1998;Zehe and Flühler, 2001a, b;Vogel et al, 2005;McGrath et al, 2007). Lateral preferential flow in soil pipe systems, which crucially determines hillslope scale subsurface runoff generation, is intermittent and is likely to be a threshold phenomenon as well (Adams and Parkin, 2002;Buttle and McDonald, 2002;Negishi et al, 2007;Weiler and McDonnell, 2007).…”
Section: Examples Of Threshold Behaviour In Hydrology and Earth Systementioning
confidence: 99%
“…Today we know of numerous studies that have provided further evidence, demonstrating that that preferential flow in structured soils is indeed the rule rather than the exception (Fig. 3) (Zachmann et al, 1987;Kladivko et al, 1991;Roth et al, 1991;Flury, 1996;Mohanty et al, 1998;Stamm et al, 1998;Stamm et al, 2002). Earthworms are as classical ecosystem engineers of special interest in this context because they build long-lasting soil structures that exert a significant influence on water flows (Edwards et al, 1990b(Edwards et al, , 1992Smettem, 1992;Shipitalo and Butt, 1999) and solute transport (Edwards et al, 1993;Zehe and Flühler, 2001a, b;Domínguez et al, 2004;Alekseeva et al, 2006;Le Bayon and Binet, 2006) but also on organic matter dynamics, pedogenetic processes and plant growth (Lavelle et al, , 2004Hedde et al, 2005;Milcu, 2005;Milcu et al, 2006).…”
Section: Infiltration and Vertical Preferential Flowmentioning
confidence: 99%
“…In soil, it is subjected to adsorption, plant uptake, weather condition, application method, movement and degradation depending on the simultaneous influence of physical, chemical and biological processes. The behavior of pesticides in soil, therefore, depends on the characteristics and overall function of the ecosystem as well as physicochemical properties of active ingredients and of its formulated products (Flury 1996;Kerle et al 2007). In addition to adsorption and biodegradation, it has been recently shown that reduced sulfur species and dissolved organic matter present in soil/sediment are capable of promoting the in situ transformation of otherwise recalcitrant pesticides (Zeng et al 2011(Zeng et al , 2012.…”
Section: Introductionmentioning
confidence: 99%